Reliability of pFET EEPROM with 70-/spl Aring/ tunnel oxide manufactured in generic logic CMOS Processes - Paulsen, Ron (IEEE Transactions on Device and Materials Reliability, 2004)
We investigate the reliability of pFET-based EEPROMs with 70-/spl Aring/ tunneling oxides fabricated in standard foundry 0.35-/spl mu/m, 0.25-/spl mu/m, and 0.18-/spl mu/m logic CMOS processes. The floating-gate memory cell uses Fowler-Nordheim tunneling erase and impact-ionization generated hot-electron injection for programming. We show that charge leakage is dominated by the leakage through interlayer dielectrics. We propose a retention model and show the data retention lifetime exceeds 10 years. These results demonstrate the feasibility of producing nonvolatile memory using standard logic processes that have a 70-/spl Aring/ oxide.